First record of Chironomus (Chironomus) calligraphus Goeldi, 1905 (Diptera: Chironomidae) from Uruguay - Martínez, María (2012)
Surveillance of the mosquito Aedes aegypti was carried out by the Ministerio de Salud Pública in all urban centers of Uruguay, from February 1997 to August 2010, as a strategy for dengue prevention. During this surveillance program the occurrence of Chironomidae was also assessed. Chironomus (Chironomus) calligraphus, was found to be sympatric with Ae. aegypti and Culex quinquefasciatus in a wide variety of artificial water containers in all sample locations within the 19 departments. This is the first record of C. calligraphus from Uruguay.